Multinational decision-making: Reconciling international norms - Donaldson, Thomas (Journal of business ethics, 1985)
How should highly-placed multinational managers, typically schooled in home country moral traditions, reconcile conflicts between those traditions and ones of the host country? When host country standards for pollution, discrimination, and salary schedules appear substandard from the perspective of the home country, should the manager take the high road and implement home country standards? Or does the high road imply a failure to respect cultural diversity and national integrity? In this paper, I construct and defend an ethical algorithm for multinational managers to use in reconciling such international normative conflicts.